Internal and Institutional Factors of Speed of Adjustment to the Target Capital Structure: Evidence from Developed and Emerging Capital Markets - КокореваМария Сергеевна; Yulova, Sonya (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2014)
<span data-sheets-value=""1":2,"2":"Kokoreva Maria Sergeevna - assistant professor, lecturer, HSE Higher School of Economics, deputy head of the school of finance, researcher of the scientific and educational laboratory of corporate finance, director of the joint educational program for the preparation of bachelors in the direction of "Economics" USU and HSE. E-mail: maria_kokoreva@mail.ru."" data-sheets-userformat=""2":513,"3":[null,0],"12":0">Authors: Kokoreva Maria Sergeevna - assistant professor, lecturer, HSE Higher School of Economics, deputy head of the school of finance, researcher of the scientific and educational laboratory of corporate finance, director of the joint educational program for the preparation of bachelors in the direction of "Economics" USU and HSE. E-mail: maria_kokoreva@mail.ru. <span data-sheets-value=""1":2,"2":"Kokoreva Maria Sergeevna - assistant professor, lecturer, HSE Higher School of Economics, deputy head of the school of finance, researcher of the scientific and educational laboratory of corporate finance, director of the joint educational program for the preparation of bachelors in the direction of "Economics" USU and HSE. E-mail: maria_kokoreva@mail.ru."" data-sheets-userformat=""2":513,"3":[null,0],"12":0">Sonia Mavletbaevna Yulova - HSE Higher School of Economics graduate, s<span data-sheets-value=""1":2,"2":"Kokoreva Maria Sergeevna - assistant professor, lecturer, HSE Higher School of Economics, deputy head of the school of finance, researcher of the scientific and educational laboratory of corporate finance, director of the joint educational program for the preparation of bachelors in the direction of "Economics" USU and HSE. E-mail: maria_kokoreva@mail.ru."" data-sheets-userformat=""2":513,"3":[null,0],"12":0">enior analyst, Business Valuation and Business Modeling Depatment, Transaction Advisory Services, EY, Moscow, Russia. E-mail: yul-sonya@yandex.ru The paper presents the results of dynamic trade-off empirical testing on the data of 30 countries for 2005-2010. The authors show that the speed of adjustment to the target capital structure for Western Europe countries is mostly determined by internal factors. Meanwhile for emerging capital market the growth rate of GDP as well as time dummy variables are crucial determinants of speed of adjustment. Institutional factors such as credit and bankruptcy institutions developments revealed nonlinear relationship with the speed of adjustment. Moreover, investor protection developmens is also a significant determinant that exhibits positive relationship for both developed and emerging markets.